A Comprehensive Evaluation of the Preanalytical Phase in Laboratory Medicine, Nephrology, Emergency Specialties, Visceral Surgery, Pediatrics, Internal Medicine and Neonatology Hospital Departments: In-Depth Insights derived from an analysis of practices at a Medical University Centre in Morocco - Rahhab, Oussama; Sebbar, El houcine; Choukri, Mohammed (Jordan Medical Journal, 2024)
Background and Aims: The precision of biological examination results hinges on meticulous preparatory measures before analysis, known as the pre-analytical phase. This phase contributes significantly to error rates (48-68%). Our study assessed the pre-analytical phase in seven hospital departments at Mohammed VI University Hospital. The objective was to address key causes of pre-analytical nonconformities. Materials and Methods: During this investigation, we observed 331 samples from various departments: Central Laboratory, Nephrology, Internal Medicine, Visceral Surgery, Emergency Specialties, Paediatrics, and Neonatology. Our evaluation identified 4945 instances of pre-analytical nonconformities. These cases encompassed issues with the prescription sheet (501), patient preparation (848), equipment preparation (295), sampling process (1957), waste management (323), and sample transfer (422). Results: Our analysis highlighted a multitude of pre-analytical nonconformities within the surveyed hospital departments. These discrepancies illuminated the critical areas where corrective and preventive measures were imperative to adhere to the standards set by the International Standard ISO15189 and to optimize patient care. Conclusions: The findings from this study underscore the paramount importance of the pre-analytical phase in ensuring accurate biological examination results. By implementing a series of targeted actions in the concerned hospital departments, we addressed the identified nonconformities. These actions encompassed ongoing education, staff awareness and support, regular audits, provision of technical resources such as manuals and sample catalogues, as well as the utilization of appropriate equipment for sample collection and transportation. Continuous learning remains essential, encompassing proper sampling techniques, packaging and transportation requisites, as well as procedures for identifying and rectifying biological sample nonconformities